2020
DOI: 10.1177/0363546520968896
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Clinical Outcomes After Hip Arthroscopy: 5-Year Follow-up Analysis of 1038 Patients

Abstract: Background: Although hip arthroscopy has been shown to have favorable results, there is a paucity of literature describing predictive factors of 5-year clinical outcomes. Purpose: To identify predictive factors of midterm outcomes after hip arthroscopy in a cohort of 1038 patients whose outcomes at minimum 2-year follow-up were previously reported. In addition, to provide a comparison of short- and midterm predictive factors in outcome measures after hip arthroscopy. Study Design: Case-control study; Level of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
54
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 82 publications
(62 citation statements)
references
References 47 publications
7
54
0
1
Order By: Relevance
“…Several previous studies have investigated risk factors for progression to THA after hip arthroscopy. One study, 8 including 860 patients with 5-year follow-up data after hip arthroscopy, found significant predictors of progression to THA to include increased age, female sex, increased BMI, revision hip arthroscopy, increased Tönnis grade, intraoperative trochanteric bursectomy, increased cartilage wear of the femoral head, and increased acetabular inclination. A case-control study 1 using a logistic regression in a cohort of 1561 hip arthroscopy procedures with a mean follow-up of 4.9 years demonstrated increasing age to be the only significant included factor in predicting progression to THA, with increased BMI, female sex, non-White race, and previous hip arthroscopy failing to show predictive significance.…”
Section: Discussionmentioning
confidence: 99%
“…Several previous studies have investigated risk factors for progression to THA after hip arthroscopy. One study, 8 including 860 patients with 5-year follow-up data after hip arthroscopy, found significant predictors of progression to THA to include increased age, female sex, increased BMI, revision hip arthroscopy, increased Tönnis grade, intraoperative trochanteric bursectomy, increased cartilage wear of the femoral head, and increased acetabular inclination. A case-control study 1 using a logistic regression in a cohort of 1561 hip arthroscopy procedures with a mean follow-up of 4.9 years demonstrated increasing age to be the only significant included factor in predicting progression to THA, with increased BMI, female sex, non-White race, and previous hip arthroscopy failing to show predictive significance.…”
Section: Discussionmentioning
confidence: 99%
“…Although all BMI groups saw a significant improvement in their pain levels, the morbidly obese group was less likely to achieve the minimal clinically important difference (MCID) for PROMs, and all 3 heftier groups were less likely to achieve the PASS and Substantial Clinical Benefit (SCB) than their normal BMI counterparts. The fourth study in this set, “Predictors of Clinical Outcomes After Hip Arthroscopy” by Domb et al, 5 also found age and BMI, among other factors, to be associated with 2- and 5-year outcome scores and conversion to arthroplasty in a series of 860 patients.…”
mentioning
confidence: 96%
“…Much additional clinical hip arthroscopy research has sought to identify other factors that might predict surgical outcomes, including general patient characteristics, preoperative hip anatomy, and preoperative or early postoperative pain or PROM levels. 5,11,13,[17][18][19][20] Most of these studies have been retrospective in design, so they identify associations that would need to be verified as truly predictive in future prospective studies. As New York Yankee great Yogi Berra is reported to have said, ''It's tough to make predictions, especially about the future.''…”
mentioning
confidence: 99%
“…10,23,31 These benefits have been well documented at short-, mid-, and long-term follow-up. 20,57 Innovative techniques have allowed for the expansion of surgical indications. 63 One such area where the indications for arthroscopy are debated is in the treatment of hip dysplasia.…”
mentioning
confidence: 99%